Impacts of health of users with HIV/AIDS in a specialized service - Maria Augusta Cunha Lima Jucá; Luciano Bairros da Silva; Ivisson Alexandre Pereira da Silva; Danlyne Eduarda Ulisses de Queiroga; Ana Márcia Agra Lemos de Carvalho; Sonia Maria Soares Ferreira (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to understand the perception of users of a Specialized Care Service (SAE- Serviço de Assistência Especializada) in HIV/AIDS about their oral health. Method: qualitative research that used the techniques of participant observation and focal group. For the analysis of the material produced, categories of analysis, construction of dialogical map and identification of linguistic repertoires were used. Results: impacts arising from oral health problems such as: inability to eat properly, feeling ashamed due to tooth loss, inability to perform physical exercises and, as the main barrier to access to dental treatment, fear of exposure to practices of discrimination and prejudice. Final considerations: we need the implementation of policies of Permanent Education to all professionals involved in the care for this population, to ensure users' rights, ensure qualified care, and create security and trust relationships with individuals living with HIV/AIDS, in access to services.